1999
DOI: 10.1212/wnl.53.3.466
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anti-α4 integrin antibody on brain lesion activity in MS

Abstract: Short-term treatment with monoclonal antibody against alpha4 integrin results in a significant reduction in the number of new active lesions on MRI. Further studies will be required to determine the longer term effect of this treatment on MRI and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
150
0
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(163 citation statements)
references
References 13 publications
3
150
0
9
Order By: Relevance
“…g/ml, 90 min pretreatment) blocks Jurkat T cell binding to fibronectin by 56±9% (n=2, data not shown) and that Jurkat cells have high expression of § 4 protein (Western analysis, not shown). Clinical trials have determined that Antegren ® , a monoclonal antibody specific for the § 4 integrin, significantly reduces the number of new brain lesions [21,22]. It is speculated that Antegren ® interferes in § 4 g 1 or § 4 g 7 interactions with the immunoglobulin superfamily member VCAM-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…g/ml, 90 min pretreatment) blocks Jurkat T cell binding to fibronectin by 56±9% (n=2, data not shown) and that Jurkat cells have high expression of § 4 protein (Western analysis, not shown). Clinical trials have determined that Antegren ® , a monoclonal antibody specific for the § 4 integrin, significantly reduces the number of new brain lesions [21,22]. It is speculated that Antegren ® interferes in § 4 g 1 or § 4 g 7 interactions with the immunoglobulin superfamily member VCAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…2) and others have shown that Rac-1 regulates T cell actin polymerization [13], we hypothesized that the Rac-1/CYFIP2 pathway regulates fibronectin-mediated binding. We chose to study fibronectin, as this protein interacts physically with § 4 and g 1 family integrin proteins [20], and recent clinical trials have shown that Antegren ® (an antibody to § 4 protein) reduced new brain lesions in MS patients as determined by MRI [21,22]. In Jurkat cells, wortmannin dose-dependently reduced Rac-1 activity ( Fig.…”
Section: Rac-1 Activity or An Increase In Cyfip2 Protein Levels Enhanmentioning
confidence: 99%
“…The results imply that therapeutic interventions targeted at interactions between T cells and ECMP (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) will be only partially effective in collagenous tissues if they do not block the costimulatory effects of type I collagen. This possibility is supported by the reports that VLA-4-blocking peptide and mAb are unable to inhibit cutaneous contact hypersensitivity, delayed-type hypersensitivity, or adjuvant arthritis in rodents by more than 35-60% (14,15,20,25).…”
Section: Discussionmentioning
confidence: 99%
“…This has led to multiple reports of the development and testing of potentially therapeutic VLA-4 Abs and peptide ligands, both in vitro and in animal models of inflammatory and autoimmune diseases, and transplantation (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Early human studies with VLA-4 targeting agents are also in progress, for example in patients with multiple sclerosis (26,27).…”
mentioning
confidence: 99%
“…Some reports have suggested that an increased level of MS disease activity (radiological disease or relapse) may occur following natalizumab cessation, even after switching to other therapies, including GA and fingolimod [13,19,28]; however, in some cases this was attributed to an initial high level of disease activity and/or few doses of natalizumab prior to interruption [11,16,18,29]. Importantly, these studies did not use monthly MRI scans to monitor subclinical disease activity.…”
Section: Timing Of Gd? Lesion Appearancementioning
confidence: 99%